Pengaruh Metode Role Playing Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas IV SDN 0704 Sungai Korang T.A 2024/2025 - Hasibuan, Roudhotul Jannah (Universitas Pahlawan Tuanku Tambusai, 2024)
This study was conducted to address issues in the student learning process, specifically the lack of variety in teaching methods, which predominantly rely on teacher lectures. As a result, students become disengaged, and their learning outcomes in the IPAS subject remain relatively low. The primary aim of this research is to evaluate whether the Role Playing method significantly affects student learning outcomes in the IPAS subject for fourth-grade students at SDN 0704 Sungai Korang for the 2024/2025 academic year. This study aims to assess the impact of the Role Playing method on students' learning achievements in the class. The research adopts a quantitative approach and involves two groups: a control class and an experimental class. The population and sample for this study consist of all fourth-grade students at SDN 0704 Sungai Korang, totaling 36 students. The research instrument is a questionnaire with 20 questions that has undergone validity testing. The findings indicate that the average score in the control class is 65.24, while in the experimental class using the Role Playing method, it is 75.53. The analysis using the 'Independent Samples Test' yields a significance (2-tailed) value of 0.008, which is less than 0.17, thus concluding that the Role Playing method has a positive impact on student learning outcomes in the IPAS subject at SDN 0704 Sungai Korang.